Psychometric Properties of the Italian Version of the Assessment of Identity Development in Adolescence (AIDA). Issue 3 (3rd July 2021) - Musetti, Alessandro; Giammarresi, Giuseppina; Goth, Kirstin; Petralia, Antonino; Barone, Rita; Rizzo, Renata; Concas, Ilaria; Terrinoni, Arianna; Basile, Consuelo; Di Maggio, Chiara; Lopez, Felipe; Terrone, Grazia; et al.
ABSTRACT: Identity diffusion is a core element of the borderline personality organization. A valid and reliable assessment tool is needed to identify at-risk adolescents in the Italian context. In this study, we investigated the psychometric properties of the Assessment of Identity Development in Adolescence (AIDA), a self-report questionnaire designed to assess identity diffusion vs. identity integration, in an Italian sample ( N = 1, 102) of clinical and nonclinical adolescents. Explorative structural equation modeling supported the expected bi-factor structure with one general factor and six descriptive factors. Scale reliability was good, with Cronbach's α = .94 for the AIDA total scale. The results supported convergent validity with measures of borderline personality features as well as discriminant validity with identity dimensions in ideological and interpersonal domains. The AIDA total score identity diffusion differed highly significantly and with a large effect size between the general population sample and patients diagnosed with borderline personality disorder ( n = 55). The Italian version of the AIDA proved to be a valid and reliable measure to assess adolescents' identity pathology within the Italian context.